Lean Thinking : Towards Achieving Value Chain Excellence in FMCG Industry - Tan, Say Yong (2007)
Value chain is a series of transformation processes that move a good or service from inception to final customer. Ideally, each step increases the worth or value of the item in the eyes of the customer. Unfortunately, non value-adding wastes always emerge at certain steps along the value chain, and customers experience (or at least perceive) a loss in value. To compete, or sometimes to survive, firm must focus on their customers, by providing them goods and services that they want, when they want it, and in the quantity they want. Lean thinking is a philosophy or a methodology that helps to deliver customer value faster, improve workflow and eliminate waste. The few keywords in lean thinking principle such as value, value stream, flow, pull, waste, just-in-time (JIT) are easy to understand but difficult to implement or achieve. However, a firm could certainly get closer to their customer’s “want” by applying these principles in their business processes, and thus achieve competitive advantage. The results so far for companies implemented lean is proven and have been impressive. In creating a truly integrated value chain, Johnson & Johnson Malaysia Consumer (JJMY) must make a mental shift from simply “what is best for my firm” to “what can I do in my firm to maximize the economic, environmental and community benefit to all the members of the value chain?” In another word, they must know how to maximize the success of all organizations in the supply chain, as a problem in one part can impact the other, and vice-versa. In order to gain better understanding of how lean thinking principle could be applied towards achieving value chain excellence, a multinational company in fast-moving consumer goods, namely Johnson & Johnson Malaysia Consumer is presented.